Clinical and diagnostic features of asthenic states in cerebrovascular diseases. - A. V. Pogorelov (Medičnì Perspektivi, 2014)
The study of 68 patients with chronic disorders of cerebral circulation (CDCC), i.e. having lacunar ischemic stroke, was carried out. It was found that patients are aware of asthenia in 57.35% and in target study asthenia is revealed without exception. The study revealed the correlation of amplitude (mcV) of P3-N3 component of visual evoked potential and clinical asthenia (r=0,41), estimated by the clinical asthenia scale MFI-20. It is concluded that in the absence of other factors of asthenia, amplitudes of long-latency phase of evoked response (P3-N3) in patients with cerebrovascular diseases may be the criterion of the so-called "neural fatigue", in order to determine the dynamics of the progression of disease and the demand in use pathogenetic therapeutic action.